Learn Not Blame: how a grassroots campaign struck a chord. (18th June 2019) - Robinson, Francesca
Abstract : In the wake of the Bawa-Garba case a campaign by the Doctors' Association UK to end blame culture in the NHS has received high profile support. Francesca Robinson reports